Elaboración de una guía metodológica de gerencia de proyectos basada en la técnica de planeación gradual para la empresa Proctek S.A.S (2015)
Methodological Guide based on the technique of Rolling wave planing for PROCTEK S.A.S company, which aims to contribute to improving the processes related to project management, allowing the organization to optimize the planning and control of projects Marco.